2017
DOI: 10.21608/asejaiqjsae.2017.4424
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Adverse Effects of Salinity in Peach Trees Grown in Saline Clay Soil

Abstract: A field experiment was carried out during 2016 and 2017 seasons on heavy clay soil, somewhat affected by salinity located at Sidi Salem District , Kafr EL-Sheikh Governorate, Egypt, to study the effect of some treatments including; Uni-sal (U), Humic acid (H), Magnetic iron (Fe) and Mycorrhizae (M) on "Florda Prince " peach trees growth, productivity and fruit quality. The data indicated that the application of these treatments increased vegetative growth parameters, leaf chlorophyll content, leaf-macro and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The best results regarding magnetic iron application in mandarin trees were gained when magnetic iron was applied at 750 g.tree −1 , followed in descending order by 500 g.tree −1 . These results are in harmony with those obtained by Soliman et al [ 15 ], who reported that magnetic iron treatment increased fruit firmness of peach trees when compared with that of the control. Magnetic iron has been reported to have a positive effect on plant growth and development [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The best results regarding magnetic iron application in mandarin trees were gained when magnetic iron was applied at 750 g.tree −1 , followed in descending order by 500 g.tree −1 . These results are in harmony with those obtained by Soliman et al [ 15 ], who reported that magnetic iron treatment increased fruit firmness of peach trees when compared with that of the control. Magnetic iron has been reported to have a positive effect on plant growth and development [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 92%
“…These findings matched those of Abobatta [ 24 ], who discovered that using magnetic iron at concentrations of 1000 g.tree −1 enhanced leaf mineral content in Valencia orange leaves compared to the control. In a similar line, Soliman et al [ 15 ] discovered that applying magnetite at a concentration of 1000 g.tree −1 once significantly enhanced leaf N, P, and K contents in Florida prince peach trees as compared to the control. Trees given magnetic iron at a concentration of 750 g.tree −1 yielded the highest significant values of nitrogen, phosphorus, potassium, and iron, while the control treatment yielded the lowest value in both seasons.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Humic acid is essential in soil organic matter which is crucial for maintaining soil fertility, which has positive impact on biological, chemical and physical properties of the soils. In addition, the nature stability of these substances affects carbon and nitrogen cycles and carbon sequestration (Soliman et al, 2017). It is produced by biodegradation of dead organic bodies.…”
Section: Introductionmentioning
confidence: 99%